Connecting Veterans and Their Community Through Narrative: Pilot Data on a Community Strengthening Intervention. - Mamon, Daria; Scoglio, Arielle A. J.; Calixte, Rachelle M.; Tuval-Mashiach, Rivka; Patton, Benjamin; Drebing, Charles E. (Community Mental Health Journal, 2020)
Military personnel transitioning to civilian life commonly report difficulty with establishing friendships, reconnecting with family, and a greater sense that they do not "fit in." Personal narrative interventions have the potential to increase the community's interest and understanding of Veterans' experience. This study examines the impact of a narrative intervention in which Veterans used film or verbal storytelling to describe their experience of being a Veteran to civilian audiences. A total 12 Veterans participated in at least one performance, and 88 community audience members attended one of six performances of the Veterans' narratives. Survey data indicate increase in positive attitudes towards Veterans, as well as a shift in the Veterans' perspective of civilians as receptive and supportive. These preliminary findings suggest that narrative interventions appear to have a positive impact on civilians' interest in Veterans and therefore, may be a valuable community reintegration intervention.